Perubahan Pola Aliran Akibat Variasi Model Baffle Block Pada Bangunan Spillway - Djunur, Lutfi Hair; Virlayani, Asnita (Universitas Kristen Indonesia Paulus, 2025)
The spillway is a hydraulic structure characterized by a channel with a steep longitudinal slope. Variations in the channel cross-section significantly influence the flow characteristics, particularly the transition from subcritical to supercritical flow conditions. A series of physical model experiments were conducted to investigate the flow behavior along the spillway structure by modifying the configuration of the baffle blocks in accordance with the standard design criteria for energy dissipation systems. High flow discharge in a steep channel generates considerable flow velocity and kinetic energy. Variations in flow pressure as water passes through the spillway structure strongly affect the downstream safety, especially concerning potential erosion of the riverbanks and channel bed. The implementation of baffle blocks along the chute effectively reduces flow energy, thereby altering flow behavior and velocity distribution over time. The findings of this study reveal that the upstream water depth is directly proportional to the energy magnitude at the downstream section of the spillway. This result demonstrates the effectiveness of the baffle blocks in dissipating flow energy, as confirmed through both analysis and experimental observations. It can be concluded that the fluid friction observed along the channel results from transitional flow phenomena occurring within the chute section.